Statistical thermodynamics fundamentals and applications - Laurendeau, Normand M., 1944- (Cambridge University Press, 2005)
Statistical Thermodynamics: Fundamentals and Applications discusses the fundamentals and applications of statistical thermodynamics for beginning graduate students. This book features a step-by-step development of the subject with each chapter carefully written to address student difficulties in learning this challenging subject. Both example and prompted homework problems are included.
Keywords: Whitman College -- Memorial bookplates -- Class of 1978.; Statistical thermodynamics.; elektronické knihy; electronic books